Antioxidant and antimicrobial properties of Casteanea sativa Miller chestnut honey produced on Mount Etna (Sicily). Issue 6 (19th March 2019) - Ronsisvalle, Simone; Lissandrello, Edmondo; Fuochi, Virginia; Petronio Petronio, Giulio; Straquadanio, Claudia; Crascì, Lucia; Panico, Annamaria; Milito, Marcella; Cova, Anna Maria; Tempera, Gianna; Furneri, Pio Maria
Abstract: The aim of this study was the evaluation of antibacterial and antioxidant properties of Monofloral Etna Castanea sativa Miller honeys. Escherichia coli ATCC 25, 922, Pseudomonas aeruginosa ATCC 27, 853, Enterococcus faecalis ATCC 29, 211 and Staphylococcus aureus ATCC 29, 213 were investigated for their susceptibilities to two different honeys. Antioxidant activity was evaluated by ORAC, NO scavenger assays, FRAP and DPPH. Antioxidant activity and antibacterial properties were compared with chestnut honeys from different geographical areas and with Manuka honey. UPLC-MS/MS was used for major components characteri sation. Abstract :